Socio-economic consequences of imported frozen tilapia in the Kenyan aquaculture value chain: Strategies for optimizing local unexploited potential - Ogello, Erick; Outa, Nicholas (My University, 2022)
The capture fisheries production sector, which is the main source of consumed fish in Kenya has been declining over the years, causing a huge deficit in fish supply in the local market. Even though aquaculture has been fronted as a stop-gap measure, there are still eminent fish supply gaps, prompting the importation of frozen tilapia, mainly from China. However, imported fish has attracted numerous socioeconomic debates between proponents and opponents of fish imports, almost in equal measure. This study investigated the socio-economic consequences of imported tilapia in the local fish market and the value chain linkages in Kisumu County. Primary data were collected using direct interviews with pre-set questionnaires fed into Open Data Kit (ODK) platform, and observations from 60 randomly selected fishermen and 60 fish farmers, 100 fish traders and 96 households. Key Informant Interviews (KII) and Focused Group Discussions (FGDs) were also conducted. About 57% of the respondents processed and traded on imported frozen tilapia, 27% of them traded on fish from capture fisheries, and 16 % traded on fish from the local aquaculture sector. Imported tilapia was the cheapest at Ksh. 200/kg compared to the locally produced tilapia at Ksh. 320/kg. At least 62 % of the households in Kisumu consumed imported tilapia regularly due to lower prices and availability. About 46 % of the respondents have gained direct employment and experienced improved socio-economic status because of the imported fish, of which 71 % are youth and women. However, about 40% of the respondents reported multiple job losses and degraded socio-economic status due to poor market for the locally produced tilapia, whether from the capture or culture sector. The study concluded that the importation of frozen tilapia can potentially reduce socio-economic returns from the local fisheries and aquaculture value chains. A rational approach is to optimize local fish production to saturate the local market and potentially out-price the imported frozen tilapia. Appropriate government policies tackling the importation of fish into the country can also help reduce the negative impacts of these imported fish on the local fish market systems.
Keywords: Fish consumption per capita; Imported fish; Tilapia; Kisumu County